2017
DOI: 10.4317/jced.53040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ex vivo effectiveness of commercial desensitizing dentifrices

Abstract: BackgroundDentin hypersensitivity is a short, severe pain with fast onset. Therapy aims to either prevent or decrease neural transmission or physically occlude the dentinal tubules. This study aimed to evaluate the effectiveness of commercial desensitizing dentifrice by means of an ex vivo method.Material and MethodsSamples (n=8 lower human premolars for each group) were randomly allocated into: G1- brushing with Colgate®Sensitive Pro-Relief; G2- brushing with Sensodyne®Rapid Relief; G3- brushing with Sensodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 22 publications
2
12
0
16
Order By: Relevance
“…In fact, as can be seen in the SEM photomicrographs, dentin tubules was partially occluded in both NaF-treated groups. This result is similar to in vitro and in vivo studies that evaluated the efficacy of fluoride products in the management of DH and found that these products decrease dentin permeability but produced only partial occlusion of dentin tubules (17,21).…”
Section: Discussionsupporting
confidence: 85%
“…In fact, as can be seen in the SEM photomicrographs, dentin tubules was partially occluded in both NaF-treated groups. This result is similar to in vitro and in vivo studies that evaluated the efficacy of fluoride products in the management of DH and found that these products decrease dentin permeability but produced only partial occlusion of dentin tubules (17,21).…”
Section: Discussionsupporting
confidence: 85%
“…5 The particle size distribution, effective diameter, and polydispersity index were also measured at 22°C (Phase Analysis Light Scattering-PALS, 90 Plus, Brookhaven Instruments Corporation, Holtsville, NY, United States) after dilution (250 mg/L) of slurries in distilled water. 19 Ten replications for the particle analyses were evaluated (n = 10).…”
Section: Chemical and Physical Analyses Of The Toothpaste Slurriesmentioning
confidence: 99%
“…O TP mostra o tamanho das partículas presentes em suspensão (MOCKDECI et al, 2017). Diversos fatores podem influenciar esse parâmetro, como: a concentração do surfactante; tipo de lipídio; propriedades do ativo a ser encapsulado e características de produção (tempo, temperatura e pressão) (MARCATO et al, 2009).…”
Section: Características Do Ensaiounclassified
“…Diversos fatores podem influenciar esse parâmetro, como: a concentração do surfactante; tipo de lipídio; propriedades do ativo a ser encapsulado e características de produção (tempo, temperatura e pressão) (MARCATO et al, 2009). De acordo com Toledo (2015), a técnica classicamente utilizada para fazer essa medida é a de No que se refere ao PZ, ele reflete a carga superficial das partículas e pode ser influenciado pela composição das mesmas, pelo meio de dispersão, pelo pH e pela força iônica presentes na solução (ANGELIERI, 2013;MOCKDECI et al, 2017). Geralmente, partículas com valores de PZ de pelo menos ± 25 mV apresentam boa estabilidade coloidal quando em suspensão (MOCKDECI et al, 2017).…”
Section: Características Do Ensaiounclassified